2014
DOI: 10.1186/1748-5908-9-73
|View full text |Cite
|
Sign up to set email alerts
|

A cluster-randomized trial of task shifting and blood pressure control in Ghana: study protocol

Abstract: BackgroundCountries in sub-Saharan Africa (SSA) are experiencing an epidemic of cardiovascular disease (CVD) propelled by rapidly increasing rates of hypertension. Barriers to hypertension control in SSA include poor access to care and high out-of-pocket costs. Although SSA bears 24% of the global disease burden, it has only 3% of the global health workforce. Given such limited resources, cost-effective strategies, such as task shifting, are needed to mitigate the rising CVD epidemic in SSA. Ghana, a country i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 30 publications
(55 reference statements)
1
69
0
2
Order By: Relevance
“…Task-shifting is a novel strategy of proven efficacy to build relevant competences in NPHW to bridge the human resource gap in the provision of services for non-communicable diseases [79] and HIV/AIDS [10] in low and middle income countries. By restructuring the workforce in this way, task shifting enables more efficient use of the available human resources.…”
Section: Introductionmentioning
confidence: 99%
“…Task-shifting is a novel strategy of proven efficacy to build relevant competences in NPHW to bridge the human resource gap in the provision of services for non-communicable diseases [79] and HIV/AIDS [10] in low and middle income countries. By restructuring the workforce in this way, task shifting enables more efficient use of the available human resources.…”
Section: Introductionmentioning
confidence: 99%
“…All the studies supported NPHWs by training them for two to six days, followed by re-training where required. 14, 54, 55 Some studies facilitated task redistribution by using mHealth technology, 14, 56 whereby NPHWs used electronic decision support tools to screen individuals in the community and link them to hypertension care. Process and interim evaluations have identified that the main barriers to task-redistribution include resistance from other health professionals; increasing NPHW workload due to additional tasks; complexity of training materials; health system-related issues such as non-availability or non-functioning BP machines, poor drug supply, lack of physician availability for referral; regulatory restrictions including the inability to prescribe medications; and low remuneration of NPHWs.…”
Section: Task Redistributionmentioning
confidence: 99%
“…44,45 Task shifting strategies have been implemented both in chronic communicable diseases such as HIV/AIDS as well as non-communicable disease conditions such as diabetes and hypertension. 46-51 However, few studies have examined the use of ABPM as part of task shifting strategies. In a recent study, James et al 52 demonstrated the feasibility of a pharmacist-led hypertension management strategy using ABPM in Ireland.…”
Section: The Potential Applicability and Current Use Of Ambulatory Blmentioning
confidence: 99%